Patient with false negative RT-PCR for COVID-19 referred to cancer hospital for lung cancer screening: A case report - Yadav, Ajay Kumar; Gnawali, Suman; Mandal, Sandip; Shrestha, Gyan Bahadur; Yuan, Gangbiao (Journal of Biomedical Sciences, 2021)
Background: Even though RT-PCR tests are generally considered the gold standard for diagnosing SARS-CoV-2, they are not without flaws, and the likelihood of detecting an infection varies depending on when the test is performed. There is chance of false negative due to different pitfalls. So there is essential of correlation of radiological characteristics, abnormalities in biochemical tests and symptoms of suspected patient during COVID-19 epidemic.Case presentation: Herein, we report a 42-year-old male patient with high-grade fever, dry cough, headache and dizziness. He went for the RT-PCR test two times and reported negative. On the chest X-Ray, there was opacity on both lungs and referred to cancer-hospital for lung-cancer screening. The patient underwent chest-HRCT and laboratory tests for further evaluation and was identified as typical COVID-19 findings. Then the patient was isolated and treatment of given according to COVID-19 treatment guidelines  Conclusion: It is concluded that a clinically symptomatic patient with typical chest HRCT and abnormal lab findings for COVID-19 should be considered as a COVID-19 patient and isolated even with two negative RT-PCR tests.